(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This article details the different roles that sport psychology may play in enhancing athleticperformance, which may then result in the growth of the sport in the nation. Resolution of the athlete’semotional conflict, mental preparation, discipline in team building, etc. are a few of the functionsmentioned in the article. The country’s sports psychologists also face issues like lack of use by sportsgroups, a meagre budget for sports, and a lack of understanding of the functions of the sportspsychologist. The paper concluded that sport psychology should be used as a method of scientificinstruction to improve athletic performance.